Poac-based management of automotive workshops to enhance students’ competence in vocational high schools - Sodiran; Iim Wasliman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to analyze the application of POAC (Planning, Organizing, Actuating, Controlling) management functions in the management of automotive workshops at SMKN 1 Cijulang and SMKN 1 Padaherang, as well as assess its contribution to improving student competence. The approach used is qualitative descriptive, with data collection techniques through in-depth interviews, participatory observations, and documentation studies. Data analysis was carried out using the Miles and Huberman interactive model which included data reduction, data presentation, and conclusion drawn, with validation through triangulation of sources and methods. The results of the study show that the implementation of management functions has been running in both schools, but it is not fully optimal. In terms of planning, limited facilities and budgets cause the goals to be not fully realistic. The organization already has a clear structure, but coordination and support personnel are still lacking. The implementation of the practice has followed the teaching factory model, but it has not been effective due to limited time and facilities. Meanwhile, supervision is still limited to technical aspects without assessing entrepreneurial competencies and soft skills. This research emphasizes the need to strengthen workshop management through collaboration with the industrial world, resource optimization, and competency-based evaluation so that vocational school graduates have high competitiveness in the world of work.